THE ADOPTION OF VIRTUAL HAJJ INNOVATION IN THE FUTURE: POTENTIALS AND CHALLENGES - Zella Famellia; Najahan Musyafak; Nadiatus Salama (Multazam : Jurnal Manajemen Haji dan Umrah, 2026)
Virtual Hajj represents a form of religious innovation arising from the integration of virtual reality (VR) technology into discourse on Hajj rituals. While prior studies have examined Virtual Hajj from technological, educational, or normative Islamic legal perspectives, limited attention has been given to its diffusion as a socio-religious innovation shaped by communication processes, religious authority, and jurisprudential norms. This study offers a conceptual and analytical prediction, rather than an empirical measurement, of the potential adoption or rejection of Virtual Hajj using Everett M. Rogers’ Innovation Diffusion Theory. Employing a qualitative literature-based approach, the study analyzes academic publications, authoritative Islamic legal opinions, and selected contextual media sources through the Miles and Huberman analytical framework. The findings indicate that the diffusion of Virtual Hajj depends on the interaction between perceived relative advantages and compatibility with Islamic normative frameworks governing ritual validity, as mediated by religious authority. The study proposes two trajectories: acceptance as a supplementary medium for ritual education or discontinuance if perceived as incompatible with established legal and ethical norms. These findings contribute to Islamic jurisprudential discourse and future Hajj policy considerations.